2010
DOI: 10.1007/s10551-010-0527-9
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Organizational Ethical Climates: How Do Managerial Practices Work?

Abstract: communication, empowerment, organizational ethical climate,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 54 publications
1
68
0
3
Order By: Relevance
“…This study was one of the few to investigate the three dimensions of organizational sustainability performance. Previous studies examining sustainability performance primarily focused on the social and financial aspects of sustainability [7]. Because sustainability has begun to encompass the triple bottom lines-social, financial, and environmental-this study therefore included environmental performance to measure a more complete framework for the sustainability performance of organizations.…”
Section: Discussionmentioning
confidence: 99%
“…This study was one of the few to investigate the three dimensions of organizational sustainability performance. Previous studies examining sustainability performance primarily focused on the social and financial aspects of sustainability [7]. Because sustainability has begun to encompass the triple bottom lines-social, financial, and environmental-this study therefore included environmental performance to measure a more complete framework for the sustainability performance of organizations.…”
Section: Discussionmentioning
confidence: 99%
“…Stevens (2008) indicated that organizational communication enhances the effectiveness of organizational codes and rules. While Parboteeah, Chen, Lee and Chung (2010) found communication is positively associated with principled-local climates and provided further evidence that principled-local ethical climates can be developed and enhanced by communication. Ethical cultures can be built if managers consider the importance of their communication in terms of transmitting and embedding an organization's assumptions and values in its employees' daily operations (Schein, 2004).…”
Section: Equity Theorymentioning
confidence: 85%
“…Through empowerment, managers can bolster employees' sense of personal responsibility for individual decisions, thus discouraging the development of egoistic-local climates and consequently reducing the incidence of ethical crises. Managers could employ empowerment practices to motivate a sense of reciprocation in their subordinates, which in turn, will elicit a benevolent-local climate in the workplace (Parboteeah, Lin, Chen, Lee, & Chung, 2010). Empowerment also signals to employees that their judgments and decisions are trusted by both the organization and their supervisors (Butts, Vandenberg, Dejoy, Schaffer, & Wilson, 2009).…”
Section: Empowerment/engagementmentioning
confidence: 99%
“…They approached it from a moral philosophy, moral psychology and sociological perspective (Parboteeah et al, 2010). For the purpose of this article it is suggested that their definition be used as the overall definition of ethical climate.…”
Section: The Construct 'Ethical Climate'mentioning
confidence: 99%